2020
DOI: 10.1101/2020.04.27.063974
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting microbiomes through a deep latent space

Abstract: Motivation: Microbial communities influence their environment by modifying the availability of compounds such as nutrients or chemical elicitors.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Deep learning techniques are actively applied in microbiome research [50–58], such as for classifying samples that shifted to a diseased state [59], predicting infection complications in immunocompromised patients [60], or predicting the temporal or spatial evolution of certain species collection [61,62]. However, to the best of our knowledge, the potential of deep learning for predicting the effect of changing species assemblages was not explored nor validated before.…”
Section: Discussionmentioning
confidence: 99%
“…Deep learning techniques are actively applied in microbiome research [50–58], such as for classifying samples that shifted to a diseased state [59], predicting infection complications in immunocompromised patients [60], or predicting the temporal or spatial evolution of certain species collection [61,62]. However, to the best of our knowledge, the potential of deep learning for predicting the effect of changing species assemblages was not explored nor validated before.…”
Section: Discussionmentioning
confidence: 99%
“…Deep learning techniques are actively applied to microbiome research [41][42][43][44][45][46][47][48][49] such as for classifying samples that shifted to a diseased state 50 , predicting infection complications in immunocompromised patients 51 , or predicting the temporal or spatial evolution of certain species collection 52,53 . However, to the best of our knowledge, the potential of deep learning for predicting the effect of changing species collection was not explored nor validated before.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, previous research has demonstrated improved predictive power can be attained by marrying different data modalities, such as microbiome, genetic, and environmental data [92]. For instance, García-Jiménez et al [93] implemented a concept of multimodal embedding by minimizing the distance between the two latent spaces created by the separate encoders of two modalities (environmental variables and microbial composition). A lineage of work on multimodal variational autoencoders investigates the most suitable way of combining the latent spaces of individual modalities depending on the dataset properties [94][95][96][97][98][99].…”
Section: Novel Techniques To Keep On the Watchlistmentioning
confidence: 99%